STRATEGI KOMUNIKASI DIGITAL HUMAS MAHKAMAH AGUNG DALAM MEMBANGUN CITRA LEMBAGA PERADILAN MELALUI INSTAGRAM - Hikmatul Rafif Hanifah; Iin Soraya; Yogi Ariska (An Nafi': Multidisciplinary Science, 2025)
The decline in public trust toward Indonesia’s judiciary largely driven by corruption scandals involving court officials has underscored the urgent need for the Public Relations division of the Supreme Court of Indonesia (Humas Mahkamah Agung RI) to adopt more effective communication strategies. This research focuses on examining how Humas Mahkamah Agung utilizes social media, specifically the Instagram account @humasmahkamahagung, to build and reinforce a positive image of the judiciary. Employing a qualitative case study approach, data were gathered through interviews, field observations, and supporting documentation. The findings reveal that Instagram serves as a strategic visual communication platform where institutional messages are shared in an organized manner, combining positive storytelling, engaging visuals, and consistent publication schedules. Despite the current limitations in facilitating two-way interactions with the public, this communication approach has successfully contributed to enhancing the public image of the judiciary. Contributing factors to this success include the availability of high- quality visual content and the presence of a professional PR team, while the main challenge remains the limited direct engagement with the public. Ultimately, this research highlights the essential role of digital communication strategies in shaping and maintaining the reputation of public institutions, especially in the era of social media that demands transparency, speed, and responsiveness to evolving legal issues.